Infoethics – a New Trend in the Science - Wyrostkiewicz, Michał (Journal of Vasyl Stefanyk Precarpathian National University, 2016)
Infoethics is a concept that arises at the interface between normative science, cognition and communication sciences and media sciences. It is a complete novelty. The conducted research recognizes it among many scientific concepts and finds its proper place and creates foundations of its research methodology